Studies of Polyvinyl Alcohol/Alkali Lignin/Silica Composite Foam Material (PLCFM) - Huachao Luo; Jing Lu; Shixue Ren; Guizhen Fang; Guiquan Jiang (BioResources, 2015)
This study investigates methods for improving the heat resistance of polyvinyl alcohol/alkali lignin foam material (PLFM). Tetraethoxysilane (TEOS) was used as a precursor to prepare PLCFM by a sol-gel method. The PLCFM, prepared with different levels of TEOS, was characterized by Fourier Transform Infrared spectrometry (FTIR), Differential Scanning Calorimetry (DSC), and Thermogravimetric Analysis (TGA). The results indicated that the addition of silica notably improved the heat resistance properties and the initial decomposition temperature of the foam and exhibited good biocompatibility with the polyvinyl alcohol (PVOH) and alkali lignin. The melting temperature of the PLCFM also increased significantly. It reached 268 °C when the silica content was 10%, which was 110 °C higher than that of PLFM. The mechanical properties were also improved to 27.42 MPa.